Establishing cutoff values for visual amyloid positivity in [18F]flutemetamol PET - Yong-Jin Park; So Young Moon; Joon-Kee Yoon; Su-Jin Lee; Young-Sil An (EJNMMI Research)
Abstract Background This study aimed to establish the optimal cutoff values for visual amyloid positivity using standardized uptake value ratios (SUVRs) in [18F]flutemetamol (FMM) positron emission tomography (PET) imaging. Given the variability in amyloid assessment, our goal was to determine cutoff values that enhance diagnostic accuracy and assist clinicians in reliably identifying amyloid positivity. Results The identified cutoff values for visual amyloid positivity were > 1.6 for the cerebellar gray matter, > 1.38 for the whole cerebellum, and > 0.63 for the pons, yielding high sensitivity (95.5%, 94.5%, and 95.8%, respectively) and specificity (91.2%, 94.3%, and 95.2%, respectively). Conclusions The SUVR cutoff values demonstrated excellent diagnostic performance, supporting their clinical use in assessing visual amyloid positivity in [18F]FMM PET imaging.